Pengaruh Persepsi Kemudahan Penggunaan, Kegunaan yang Dirasakan dan Tingkat Pendidikan Terhadap Niat Berbelanja Kembali Pada Situs Tokobagus.com - Wicaksana, I Made Rendy; Santika, I Wayan (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
1024x768 Purposed of this study is to determine the effect of perceive ease of use, perceive usefulness, and level of education against intention to buy online again in Tokobagus.com in Denpasar, the samples taken were 110 people with purposive sampling method. Data was collected through questionnaires using a 5-point Likert scale to measure 11 indicators. The analysis technique used is multiple linear regression. These results indicate that each variable perceive ease of use, perceive usefulness, and level of education positive and significant effect on intention to buy online again. This suggests that the effect of perceive ease of use, perceive usefulness, and level of education can increase intention to buy online again. Keywords : Perceive ease of use, perceive usefulness, level of education, intention to buy again. Normal 0 false false false IN X-NONE X-NONE